Lithium bis(trifluoromethanesulfonyl)imide blended in polyurethane acrylate photocurable solid polymer electrolytes for lithium-ion batteries - Mendes-Felipe, Cristian (2021)
The increased demand of electronic devices promotes the development of advanced and more efficient energy storage devices, such as batteries. Lithium-ion batteries (LIBs) are the most studied battery systems due to their high performance. Among the different battery components, the separator allows the control of lithium ion diffusion between the electrodes. To overcome some drawbacks of liquid electrolytes, including safety and environmental issues, solid polymer electrolytes (SPEs) are being developed. In this work, a UV photocurable polyurethane acrylate (PUA) resin has been blended with lithium bis(trifluoromethanesulfonyl) imide (LiTFSI) up to 30 wt% LiTFSI content to reach a maximum ionic conductivity of 0.0032 mS/cm at room temperature and 0.09 mS/cm at 100 ºC. Those values allowed applying the developed materials as photocurable SPE in Swagelok type Li/C-LiFePO4 half-cells, reaching a battery discharge capacity value of 139 mAh.g -1 at C/30 rate. Those results, together with the theoretical studies of the discharge capacity at different C-rates and temperatures for batteries with LiTFSI/PUA SPE demonstrate the suitability of the developed photocurable SPE for LIB applications.